Investigation of Serum TNF-alpha, TRAF-1, andTRAF-2 in Patients Suffer from Ulcerative Colitis - Iqbal, Mayada Noori; Mahdi, Liwaa Hussein; Eidan , Ali Jabbar (Kufa Journal for Nursing Sciences, 2016)
Background: Ulcerative colitis (UC) is a chronic inflammatory disease of unknown causes. It has involved the inflammatory process of the mucosa and sometimes the submucosa of the large intestinal tract. There are a several theories involve role of the immune mechanisms and cell signals that lead to activation of many intracellular adapter proteins and other markers, which in turn trigger an inflammatory process and death of many colonocytes. Objective: investigation of serum TNF-alpha, TRAF-1 and TRAF-2 levels in active Ulcerative Colitis and also, identified the diagnostic possibility of the studied parameters in diagnosis of UC patients. Methodology: A case-control study was conducted at the City of Al-Najaf Al-Ashraf using 56 and 30 individuals of both genders for Patients and Control groups with an overall age range of 18-75 years old. All sera with negative Epstein-Barr Virus (EBV) agglutination test of all subjects were monitored for level of Tumor Necrosis Factor-alpha (TNF), TNF Receptor Associated Factor-1 (TRAF-1), and TNF Receptor Associated Factor-2 (TRAF-2), by ELISA Method. All these Data was analyzed by using spss (T-test) program and also, the receiver operate characteristic curve (ROC) was used to identify their possibility of diagnostic value. Results: Serum level of TNF-alpha, TRAF-1 and TRAF-2 were significantly higher in UC patients than those in controls (P values were = 0.000). TNF-alpha, TRAF-1, and TRAF-2 shown to have a display to fabulous value in the differentiation of UC patients and control with the area under the ROC curve (AUR) of 0.698–1.000 (P value < 0.001). Conclusion: In light of the obtained results in current study, we conclude that the serological levels of TNF-alpha, TRAF-1 and TRAF-2 were increased in active UC patients. It seems that the activation of TNF-alpha, TRAF-1, and TRAF-2 may be first events in the development of UC. Recommendation: Additional genetic and immunological markers, including standardized lymphocytes and other assays, are needed. These are to determine the pro-inflammatory cytokines and monitor the progress of the disease in order to detect the suitable time of a possible intervention.